2014
DOI: 10.1038/ncomms5629
|View full text |Cite|
|
Sign up to set email alerts
|

YAP inhibits squamous transdifferentiation of Lkb1-deficient lung adenocarcinoma through ZEB2-dependent DNp63 repression

Abstract: Whether the Hippo pathway contributes to cell lineage transition under pathological conditions, especially tumorigenesis, remains largely unknown. Here we show that YAP, the major effector of the Hippo pathway, displays a distinct activation pattern in lung adenocarcinoma (ADC) and squamous cell carcinoma (SCC); YAP is initially activated by LKB1 loss in lung ADC, which upregulates ZEB2 expression and represses DNp63 transcription in a default manner. During transdifferentiation, YAP is inactivated, which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 49 publications
7
105
0
Order By: Relevance
“…Instead of studying cancer metastasis, our work focuses on the role of Yap in tumor formation using the Kras G12D /Lkb1 L/L mouse model, in which the de novo lung ADC can progressively transdifferentiate into SCC. Our recent work has shown that Yap knockdown using lenti-shRNA delivery in KL mice promotes the ADC to SCC transdifferentiation (23). In contrast, homozygous deletion of YAP in this model resulted in a dramatic inhibition of lung ADC progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of studying cancer metastasis, our work focuses on the role of Yap in tumor formation using the Kras G12D /Lkb1 L/L mouse model, in which the de novo lung ADC can progressively transdifferentiate into SCC. Our recent work has shown that Yap knockdown using lenti-shRNA delivery in KL mice promotes the ADC to SCC transdifferentiation (23). In contrast, homozygous deletion of YAP in this model resulted in a dramatic inhibition of lung ADC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted and retro-transcribed into first-strand complementary DNA as previously described (23). cDNAs were subjected to quantitative real-time PCR with gene-specific primers on the 7500 Fast Real-Time PCR System using SYBR-Green Master PCR mix.…”
Section: Rt-pcr and Quantitative Real-time Pcrmentioning
confidence: 99%
“…3D). In addition, a recent study reported a ZEB2-dependent suppression of ⌬Np63 promoter by YAP (TAZ paralog) during squamous transdifferentiation of lung epithelial cells (60). These studies suggest that TAZ, like YAP, may also suppress cellular gene transcription through interacting with other transcription factors.…”
Section: Taz Is a Dual Regulator Of Gene Transcription-studies Havementioning
confidence: 95%
“…There is ample evidence that deregulation of the LKB1 signaling pathway appears to play a major role in tumor pathogenesis, since it facilitates malignant development through suppression of cell apoptosis and growth arrest (27)(28)(29)(30). To investigate the oncogenic state of the L02 cell line, functional assays were carried out including evaluation of the clonogenicity and tumor-initiating potential.…”
Section: Discussionmentioning
confidence: 99%
“…anchorage-independent growth in soft agar is one of the hallmark characteristics of cellular transformation and uncontrolled cell growth, with normal cells typically not capable of growth in semi-solid matrices (26). Recent studies have provided compelling evidence that loss of LKB1 activity is a critical step in oncogenesis (27)(28)(29)(30). To explore the oncogenic potential of LKB1-deficient L02 cells, a soft agar colony formation assay was carried out.…”
Section: Ectopic Lkb1 Expression Blocks Rb Phosphorylation In the L02mentioning
confidence: 99%